Strangers “at home”: Gay, lesbian and bisexual students’ strategies for resisting heteronormativity in university residence life - Munyuki, C.; Vincent, L. (South African Journal of Higher Education, 2018)
Higher education in post-apartheid South Africa has been concerned with the establishment of non-discriminatory institutions. However, research continues to highlight various experiences of exclusionary practices across universities in South Africa. In this article, we demonstrate the various coping mechanisms that some students who self-identify as gay, lesbian or bisexual in the university residences adopt to deal with the exclusionary practices that the dominant heteronormative culture of the institution (re)produces which positions them as “sexual strangers” within the institutional “home”. We adopt Vangelisti and Crumley’s (1998) three categories of behaviour namely “acquiescence” which we term here as endeavours to “fit in”, “invulnerability” which we identify as “keeping one’s distance”, “verbal active” as “voicing” and a fourth category we identify as “turning the tables on heteronormativity” in our discussion. We also highlight the various forms of responses that the institution adopts in its attempts to create a conducive environment for all.